ETV1 Positively Correlated With Immune Infiltration and Poor Clinical Prognosis in Colorectal Cancer - Shen, Xiaonan; Zhou, Chunhua; Feng, Haoran; Li, Jialu; Xia, Tianxue; Cheng, Xi; Zhao, Ren; Zou, Duowu (Frontiers in Immunology, 2022)
Objective: Numerous studies recently suggested that immune microenvironment could influence the development of colorectal cancer (CRC). These findings implied that the infiltration of immune cells could be a promising prognostic biomarker for CRC. Methods: Furthermore, Oncomine database and R2 platform analysis were applied in our research to validate CRC clinical prognosis via expression levels of PEA3 members. We expolred the correlation of ETV1, ETV4 and ETV5 with tumour infiltrating immune cells (TIICs) in CRC tumour microenvironments via TIMER (Tumor Immune Estimation Resource) and GEPIA (Gene Expression Profiling Interactive Analysis). Immunohistochemistry (IHC) was used to validate our CRC clinical data. Results: Our findings indicated that the upregulation of PEA3 members including ETV1 and ETV5 was positively associated with poor prognosis in CRC patients. Meanwhile ETV1 and ETV5 may play significant roles in the development progress of CRC. Furthermore, ETV1 tend to be associated with immune infiltration of colorectal cancer, especially with cancer associated fibroblasts and M2 macrophages. Conclusion: These findings revealed that ETV1 and ETV5 played significant roles in the development of CRC and ETV1 was significantly associated with the infiltration of cancer associated fibroblasts and M2 macrophages in colorectal cancer. Targeting ETV1 can be a potential auspicious approach for CRC treatment.